Role of Galectin-3 in Obesity and Impaired Glucose Homeostasis. (6th December 2015) - Menini, Stefano; Iacobini, Carla; Blasetti Fantauzzi, Claudia; Pesce, Carlo M.; Pugliese, Giuseppe
Abstract : Galectin-3 is an important modulator of several biological functions. It has been implicated in numerous disease conditions, particularly in the long-term complications of diabetes because of its ability to bind the advanced glycation/lipoxidation end products that accumulate in target organs and exert their toxic effects by triggering proinflammatory and prooxidant pathways. Recent evidence suggests that galectin-3 may also participate in the development of obesity and type 2 diabetes. It has been shown that galectin-3 levels are higher in obese and diabetic individuals and parallel deterioration of glucose homeostasis. Two studies in galectin-3 knockout mice fed a high-fat diet (HFD) have shown increased adiposity and adipose tissue and systemic inflammation associated with altered glucose homeostasis, suggesting that galectin-3 negatively modulates the responsiveness of innate and adaptive immunity to overnutrition. However, these studies have also shown that impaired glucose homeostasis occurs in galectin-3 knockout animals independently of obesity. Moreover, another study reported decreased weight and fat mass in HFD-fed galectin-3 knockout mice. In vitro, galectin-3 was found to stimulate differentiation of preadipocytes into mature adipocytes. Altogether, these data indicate that galectin-3 deserves further attention in order to clarify its role as a potential player and therapeutic target in obesity and type 2 diabetes.